Impact of Growth Opportunities and Competition on Firm-Level Capability Development Trade-offs - Rahmandad, Hazhir (Organization Science, 2012)
How should managers prioritize among production, product development, branding, internationalization, and other capabilities and resources? This question is central to the resource-based view, and the answer depends not only on the direct returns on investment in each capability but also on the trade-offs in using those returns for future growth or survival in a competitive market. Through simulation experiments, this study examines firm-level capability development trade-offs in the context of a firm's market-level competition and growth. It is found that investing in operational capabilities (which enhance short-term performance) gains priority over investing in long-term dynamic capabilities when the operational capability investment strengthens the reinforcing loop between performance, investment flow, and capability development. Such operational capability investment provides growth opportunities and competitive advantage. Moreover, in strategic competition, firms anticipating rivals' focus on short-term growth need to further ignore dynamic (long-term) capability building in order to survive. Testable propositions are offered as to how trade-offs between short-term and long-term investments depend on different firm and industry characteristics. The results may explain why short-term-focused firm behavior persists in firms even in the absence of discounting, short-term managerial incentives, decision biases, or learning failures.